(untitled) (Web of Teachers: Inderscience Research, 2026)
This thesis examines the appearance of the software and methodological complex for "Computational Methods" taught in higher education institutions, experimental research work, and educational content of the platform. Also, the methodological guide "Methodological recommendations for working on the Hisobly platform" on the use of the software and methodological complex was reviewed.